SPECIFICS OF PRE-ADMISSION EMERGENCY CARE IN PATIENTS WITH ATRIAL FIBRILLATION - V. G. Yepifanov; V. T. Dolgikh (Российский кардиологический журнал)
Aim. To perform a retrospective comparison of pre-admission emergency care tactics and outcomes in patients with uncomplicated atrial fibrillation (AF) episodes. Material and methods. In total, 1200 cases of pre-admission emergency care in AF patients were analysed, using the ambulance call forms, polyclinics medical cards, and hospital case histories. The emergency care outcomes were compared for the patients who were not hospitalised and those were admitted to the hospital within 1, 12, or 24 hours. Results. The pre-admission emergency care in patients with uncomplicated AF was not effective within the first hour of the follow-up. In over 90% of the cases, AF episode was resolved within 24 hours, regardless of the emergency care tactics or the antiarrhythmic drug used. Inadequate ventricular rate reduction at the preadmission stage was associated with a longer AF episode duration and an increased chance of hospitalisation. Conclusion. The tactics of pre-admission emergency care in uncomplicated AF episodes lasting under 24 hours should primarily address the reduction of ventricular rate. The strategy of obligatory hospitalisation of all ambulanceattended uncomplicated AF episodes which lasted less than 24 hours is not just